"Preventing the Pain" When Working with Family and Sexual Violence in Primary Care. (28th January 2013) - Coles, Jan; Dartnall, Elizabeth; Astbury, Jill
Abstract : Primary care professionals (PCPs) are increasingly being expected to identify and respond to family and sexual violence as the chronic nature and severity of the long-term health impacts are increasingly recognized. This discussion paper reports the authors' expert opinion from their experiences running international workshops to prevent trauma among those who work and research sexual violence. It describes the burnout and secondary traumatic stress literature which provides the evidence supporting their work. Implications for practicing basic training in response to trauma and ongoing education are a key area for responding to family violence and preventing professional stress. A professional culture that supports and values caring well for those who have experienced family violence as well as "caring for the carer" is needed. Working in teams and having more support systems in place are likely to protect PCPs from secondary traumatic stress and burnout. Undergraduate and postgraduate training of PCPs to develop trauma knowledge and the skills to ask about and respond to family violence safely are essential. In addition, the healthcare system, workplace, and the individual practitioner support structures need to be in place to enable PCPs to provide safe and effective long-term care and access to other appropriate services for those who have experienced family violence.